VILAR, Gerard (2019). Jean-François Lyotard: Estètica i política, Barcelona: Gedisa, 144 pp. - Meijide Casas, Sergio (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: VILAR, Gerard (2019). Jean-François Lyotard: Estètica i política, Barcelona: Gedisa.